2021
DOI: 10.3390/ijerph18094702
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Audiometry for Early Detection of Hearing Loss: A Narrative Review

Abstract: The WHO considers hearing loss to be a major global problem. A literature search was conducted to see whether high-frequency audiometry (HFA) could be used for the early detection of hearing loss. A further aim was to see whether any differences exist in the hearing threshold using conventional audiometry (CA) and HFA in workers of different age groups exposed to workplace noise. Our search of electronic databases yielded a total of 5938 scientific papers. The inclusion criteria were the keywords “high frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…Study limitations include relatively small numbers of individuals in individual age/sex groups. As otitis media can also affect hearing [ 21 ], the fact that we did not collect anamnestic data about otitis in the history of individual patients can also be considered a limitation to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations include relatively small numbers of individuals in individual age/sex groups. As otitis media can also affect hearing [ 21 ], the fact that we did not collect anamnestic data about otitis in the history of individual patients can also be considered a limitation to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many study findings remarkably confirmed the concept that EHFA hearing thresholds may be more sensitive for early detection of hearing damage than conventional PTA at lower frequencies. [ 24 25 26 27 ] However, there is a dearth of evidence assessing the relationship between hypertension and hearing loss using EHFA. To the best of our knowledge, only one population-based study has used EHFA testing to investigate the relationship between hearing sensitivity and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…While the equipment for conducting clinical audiometric tests is widely available, that for assessing hearing at the EHFs is more expensive and not widely available. The use of EHF audiometry as an early indicator of NIHL is still controversial, but our results, as well as previous studies, 37 , 38 suggest that EHF audiometry (from 9-20 kHz) could identify the first signs of NIHL, especially at 12.5 to 18 kHz. We conducted a large-scale study on shipyard workers in China aged 20 to 60 years, on the assumption that people in this age range would be old enough for noise exposure effects to be measurable but young enough that aging effects would be minimized.…”
Section: Discussionmentioning
confidence: 99%